Relationship between leadership styles of head and teachers’ job satisfaction in the public colleges of district Lahore - Noreen , Iqra (American Journal of Social Sciences and Humanities, 2025)
Leadership encompasses the ability to influence individuals in pursuit of defined educational and institutional objectives. This study aimed to ascertain the leadership styles of principals in colleges, assess the job satisfaction levels of college educators, and examine the correlation between leadership style of head and the job satisfaction of teachers. A descriptive research design was employed for this investigation. The study’s population comprised public colleges located in the Lahore district. Proportionate multistage stratified random sampling method was used to choose the sample by the researcher. The researcher evolved two questionnaires to probe the relationship between job satisfaction and leadership styles, both of which demonstrated a reliability coefficient of 0.91. Data collection was conducted through personal visits to public sector colleges. The Pearson Coefficient Product Moment was applied to analyze the correlation among leadership styles and job satisfaction. Furthermore, to investigate variations in demographic characteristics pertaining to leadership style and work satisfaction among college teachere in Lahore, independent sample t-tests were utilized.The results indicated a significant, positive, and robust relationship between heads’ leadership style and the job satisfaction of teachers. Both transformational and transactional leadership styles were found to be strongly associated with teachers’ job satisfaction. Results of the study showed female teachers are more satisfied than male. It is essential to emphasize effective leadership styles, accompanied by appropriate guidance and supervision, to enhance job satisfaction, as satisfied teachers are more likely to perform their duties effectively and contribute significantly to achieving educational objectives.